Corporate Growth, Age and Ownership Structure: Empirical Evidence in Spanish Firms - de Jorge Moreno, Justo (2012)
The objective of this work is to analyse firm mobility among the different sectors of the Spanish economy according to a statistical classification of economic activities at the 1-digit level. Some of the stylised facts that we find are: an inverse relation between firm growth and age; an increase in new entrants' average relative size in terms of sales compared to established firms among the different industries and cohorts; the importance of the firm's initial size in entrepreneurial activity; the favourable impact of the economy on firm growth; and a positive relation between non-concentration in the ownership structure and greater mobility. In this context, an efficient corporate governance system may prove as a significant policy tool for the investment and growth prospective of the Spanish economy. The regulatory framework of the Spaniard capital market has been coordinate with the EU standards. The challenge is now mostly for the firms to adopt the appropriate corporate governance structures, in order to achieve real convergence, in terms of productivity and competitiveness, with other developed economies.